Rethinking the role of zakat in poverty eradication - Ku ‘Azam Tuan Lonik; Nor Syafinas Muda (Proceedings of AICS - Social Sciences, 2013)
Malaysia has done very well in eradicating the problem of poverty in the country. The poverty rate has fallen from 49.3 percent in 1970 to 3.9 percent in 2009. Nonetheless, one main facet of such phenomenon remains, i.e. the majority of the poor are from the Malay-Muslim community. In Malaysia, the management of zakat is under the state jurisdiction. As such the collection and disbursement of the zakat funds also falls under the purview of the Majlis Agama Islam Negeri. Each of the Majlis Agama Islam Negeri has its own zakat collection body. Two issues emerged. First, while zakat should be able to free the recipient from poverty, yet, the proportion of money allocated for these groups of asnaf is very minimal such that it fails to uplift the economic well-being of the recipients. Second, current practices adopted by most zakat agency are to give cash money to the recipients which failed to motivate them to embark on productive activities to uplift their economic well-beings. This paper evaluate the attempt made to provide start-up capital for the poor to engage in business activities using the zakat fund in the hope that the success of the initiatives will see a reduction in the incidence of poverty among the muslim communities and to ensure that the money disbursed to the poor and the needy are used not for consumptive purpose but for productive activities.Keywords: zakah, poverty, poor and needy